MODELING THE DEVELOPMENT OF COMMUNICATION AND INFORMATION PROCESSES IN THE PUBLIC FIELD (Proceedings of International Educators Conference, 2024)
The theoretical foundations of the mechanisms for the development of communication and information services using digital technologies in the field of housing and communal services of the region have been improved. Medium-term multi-variant scenarios for the development of the communication and information system for the provision of housing and communal services to the residents of the region have been developed.